2009
DOI: 10.1016/j.nimb.2009.02.043
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation of small carbon clusters, a review

Abstract: International audienceAn overview of the works devoted to fragmentation of small carbon clusters is given in a first part. Fragmentation of swift neutral and (multi) charged carbon clusters studied with the AGAT spectrometer is presented and discussed in a second part. (C) 2009 Elsevier B.V. All rights reserved

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Similar results were reported in [51]. High energy collisions give similar results up to the measured largest cluster N = 10, as reported in [52]. A study using collision induced dissociation showed C 5 as the main loss channels for C + 16 and C + 19 [53].…”
Section: Discussion and Summarysupporting
confidence: 89%
“…Similar results were reported in [51]. High energy collisions give similar results up to the measured largest cluster N = 10, as reported in [52]. A study using collision induced dissociation showed C 5 as the main loss channels for C + 16 and C + 19 [53].…”
Section: Discussion and Summarysupporting
confidence: 89%
“…This energy is resulting from both inner valence holes and electronic excitations. For small carbon clusters (n=2 to 10), the first contribution (inner valence holes) has been calculated in Béroff et al (2009). Dipole approximation in the collision was assumed.…”
Section: Internal Energy Following Multi-ionizationmentioning
confidence: 99%
“…Likewise, C 7 + -C 9 + appear simultaneously and then track together, C 10 + -C 12 + appear and track together, and so on. Given that carbon cluster ions readily fragment in the gas phase, [47][48][49][50][51][52] it is important to ascertain the degree to which the observed droplet size dependence of the distributions are influenced by ion fragmentation processes. Previously, it has FIG.…”
Section: Assembly Of Carbon Clustersmentioning
confidence: 99%